Curcumin- and Cyclopamine-Loaded Liposomes to Enhance Therapeutic Efficacy Against Hepatic Fibrosis - Zhang T; Li Y; Song Y; Chen X; Li J; Peng Q; He J; Fei X (Dove Medical Press, 2020)
Ting Zhang,1 Yanping Li,2 Yi Song,1 Xiaoshuang Chen,1 Jing Li,1 Qiang Peng,3 Jinhan He,1,2 Xiaofan Fei1 1Department of Pharmacy, West China Hospital, Sichuan University, Chengdu 610041, People’s Republic of China; 2Laboratory of Clinical Pharmacy and Adverse Drug Reaction, West China Hospital of Sichuan University, Chengdu, People’s Republic of China; 3State Key Laboratory of Oral Diseases, West China Hospital of Stomatology, Sichuan University, Chengdu 610041, People’s Republic of ChinaCorrespondence: Xiaofan Fei Tel + 86-28-85423475Email 1145342867@qq.comBackground and Purpose: Hepatic fibrosis is a public health problem characterized by activation of hepatic stellate cells (HSCs), which triggers excessive production of extracellular matrix (ECM). Inhibition of HSC activation may be an effective treatment. Since various pathways control HSC activation, a combination of drugs with different mechanisms may be more effective than monotherapy.Methods: Here, we prepared liposomes loaded with curcumin and cyclopamine to inhibit HSC activation. We systematically analyzed the physicochemical characteristics of liposomes loaded with the two drugs, as well as their effects on HSC proliferation, activation and collagen production on gene, protein and cellular levels.Results: The prepared liposomes helped solubilize both drugs, contributing to their uptake by cells. Liposomes loaded with both drugs inhibited cell proliferation, migration and invasion, as well as induced more apoptosis and perturbed the cell cycle more than the free combination of both drugs in solution or liposomes loaded with either drug alone. Liposomes loaded with both drugs strongly suppressed HSC activation and collagen secretion.Conclusion: Our results suggest that liposome encapsulation can increase the uptake of curcumin and cyclopamine as well as the synergism between them in anti-fibrosis. This approach shows potential for treating hepatic fibrosis.Keywords: hepatic stellate cells, HSCs, hepatic fibrosis, cyclopamine, curcumin, synergistic effect